Dexmedetomidine protects H9c2 cardiomyocytes against oxygen-glucose deprivation/reoxygenation-induced intracellular calcium overload and apoptosis through regulating FKBP12.6/RyR2 signaling - Yuan M; Meng XW; Ma J; Liu H; Song SY; Chen QC; Liu HY; Zhang J; Song N; Ji FH; Peng K (Dove Medical Press, 2019)
Mei Yuan,1,2,* Xiao-Wen Meng,1,* Jiao Ma,1,* Hong Liu,3 Shao-Yong Song,1 Qing-Cai Chen,1 Hua-Yue Liu,1 Juan Zhang,1 Nan Song,1 Fu-Hai Ji,1 Ke Peng11Department of Anesthesiology, First Affiliated Hospital of Soochow University, Suzhou, Jiangsu 215006, People’s Republic of China; 2Department of Anesthesiology, Affiliated Suzhou Hospital of Nanjing Medical University, Suzhou, Jiangsu 215008, People’s Republic of China; 3Department of Anesthesiology and Pain Medicine, University of California Davis Health System, Sacramento, CA 95817, USACorrespondence: Fu-Hai Ji; Ke PengDepartment of Anesthesiology, First Affiliated Hospital of Soochow University, 188 Shizi Street, Suzhou, Jiangsu 215006, People’s Republic of ChinaTel +86 5 126 778 0055; +86 5 126 778 0159Email jifuhaisuda@163.com; pengke0422@163.com*These authors contributed equally to this workPurpose: Intracellular calcium ([Ca2+,]i) overload is a major cause of cell injury during myocardial ischemia/reperfusion (I/R). Dexmedetomidine (DEX) has been shown to exert anti-inﬂammatory and organ protective effects. This study aimed to investigate whether pretreatment with DEX could protect H9c2 cardiomyocytes against oxygen-glucose deprivation/reoxygenation (OGD/R) injury through regulating the Ca2+, signaling.Methods: H9c2 cardiomyocytes were subjected to OGD for 12 h, followed by 3 h of reoxygenation. DEX was administered 1 h prior to OGD/R. Cell viability, lactate dehydrogenase (LDH) release, level of [Ca2+,]i, cell apoptosis, and the expression of 12.6-kd FK506-binding protein/ryanodine receptor 2 (FKBP12.6/RyR2) and caspase-3 were assessed.Results: Cells exposed to OGD/R had decreased cell viability, increased LDH release, elevated [Ca2+,]i level and apoptosis rate, down-regulated expression of FKBP12.6, and up-regulated expression of phosphorylated-Ser2814-RyR2 and cleaved caspase-3. Pretreatment with DEX significantly blocked the above-mentioned changes, alleviating the OGD/R-induced injury in H9c2 cells. Moreover, knockdown of FKBP12.6 by small interfering RNA abolished the protective effects of DEX.Conclusion: This study indicates that DEX pretreatment protects the cardiomyocytes against OGD/R-induced injury by inhibiting [Ca2+,]i overload and cell apoptosis via regulating the FKBP12.6/RyR2 signaling. DEX may be used for preventing cardiac I/R injury in the clinical settings.Keywords: dexmedetomidine, H9c2 cardiomyocytes, oxygen-glucose deprivation/reoxygenation, apoptosis, intracellular calcium overload, FKBP12.6/RyR2